1998
DOI: 10.1124/mol.53.1.105
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Novel Protein Kinase C Isozymes in Influencing Sensitivity of Breast Cancer MCF-7 Cells to Tumor Necrosis Factor-α

Abstract: Protein kinase C (PKC) has been implicated in tumor necrosis factor-␣ (TNF) signaling. Structurally and functionally distinct PKC activators and selective inhibitors of PKC were used to investigate the involvement of PKC isozymes in influencing TNF sensitivity in MCF-7 cells. Activators of PKC, such as phorbol-12,13-dibutyrate (PDBu) (1.0 M), indolactam V (10 M), and bryostatin 1 (1.0 M) decreased the sensitivity of MCF-7 cells to TNF by 5-, 10-, and 1.7-fold, respectively. The PKC-specific inhibitor bisindoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Unique up-regulation of PKC-has been noted previously in interleukin 2-producing EL4 mouse thymoma cells (12), in murine keratinocytes (39), and in breast cancer lines (40), and the lack of down-regulation was observed also in A431 human epidermal carcinoma cells (41). Basu (40) observed down-regulation of PKC-after treatment of MCF-7 cells with BIM, but we did not see a BIM-induced down-regulation of PKC-expression in the astrocytic cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Unique up-regulation of PKC-has been noted previously in interleukin 2-producing EL4 mouse thymoma cells (12), in murine keratinocytes (39), and in breast cancer lines (40), and the lack of down-regulation was observed also in A431 human epidermal carcinoma cells (41). Basu (40) observed down-regulation of PKC-after treatment of MCF-7 cells with BIM, but we did not see a BIM-induced down-regulation of PKC-expression in the astrocytic cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Activation of PKC⑀ Is Necessary for Its Antiapoptotic Action-We have previously shown that PKC activators protect cells against TNF-induced cytotoxicity (22). Fig.…”
Section: Figmentioning
confidence: 99%
“…Phase II clinical trials of bryostatin 1 are under way for the treatment of leukemias, lymphomas, melanomas, and solid tumors (26). Bryostatin 1 also shows promise for treatment of ovarian and breast cancers and for enhancing lymphocyte survival during radiation treatment (3,4,5,12,13,16,20,21,28,32,33). Other bryostatins may prove to be valuable therapeutic agents as well (19).…”
mentioning
confidence: 99%